Pyranonaphthoquinone and anthraquinone derivatives from Ventilago harmandiana and their potent anti-inflammatory activity - Kanda Panthong (2020)
© 2019 Elsevier Ltd The chemical study on the heartwoods extract of Ventilago harmandiana (Rhamnaceae) resulted in the isolation of ten previously undescribed pyranonaphthoquinones (ventilanones A−J), an undescribed anthraquinone (ventilanone K), together with eight known anthraquinone derivatives. Their structures were elucidated by extensive analysis of their spectroscopic data. The absolute configuration of ventilanone A was established from single crystal X-ray crystallographic analysis of its p-bromobenzenesulfonate ester derivative using Cu Kα radiation. The absolute configurations of the other related compounds were identified by comparison of their ECD data with those of ventilanone A and related known compounds. Cytotoxic and anti-inflammatory activities of some of the isolated compounds were evaluated. Ventilanone A and ventilanone C exhibited moderate cytotoxicity against P-388 cell line. Ventilanone D exhibited significant anti-inflammatory activity while ventilanone A and ventilanone C showed moderate activity.